Exposure to fenvalerate and tebuconazole exhibits combined acute toxicity in zebrafish and behavioral abnormalities in larvae - Yao, Chunlian; Huang, Lan; Li, Changsheng; Nie, Dongxing; Chen, Yajie; Guo, Xuanjun; Cao, Niannian; Li, Xuefeng; Pang, Sen (Frontiers in Environmental Science, 2022)
In aquatic ecosystems, pesticide residues meanly present as mixtures of varying complexity, which may lead to compound pollution of organisms. Therefore, it is of great practical importance to evaluate the combined toxic effects of pesticides. In this study, the mixture acute toxicities of fenvalerate with tebuconazole on zebrafish larvae and adults were investigated. The effects of mixture toxicity on swimming behavior of larvae were also analyzed. The mixture acute toxicity of the systems showed antagonistic effects on adult zebrafish when the mixing ratios of fenvalerate and tebuconazole were equal, but the other two ratios of the mixes both showed synergistic effects. The strongest synergistic effect was observed when fenvalerate was mixed with tebuconazole in the ratio of 8:2. The swimming behavior of zebrafish larvae was significantly inhibited after exposure to single or mixed systems for 2 days. However, significant up-regulation of behavioral indicators in zebrafish larvae was observed at the beginning of exposure in the mixture exposure groups. The results showed that fenvalerate and tebuconazole had the risk of synergistic toxic effect on zebrafish. It is recommended that the simultaneous use of both pesticides in agricultural activities near water bodies should be scientifically controlled to avoid adverse effects on aquatic organisms.